RESEARCH AND ANALYSIS OF FLUXES FOR SURFACING TRAVELING WHEELS OF OVERHEAD CRANES - PhD. Xashimov Xalimjon Xamidjanovich; Bahromjon Ayubov Rustam ogli (European Science Publishing, 2024)
The article deals with the issue of surfacing under the ceramic flux of the wheels of overhead cranes. Worn parts cause the machines to work with a deviation from the specified parameters, reduce the efficiency of the machines, lead to the emergence of additional load units of the machines, due to which it leads to a deterioration in the working conditions and weakening of the mechanisms of the machines. To prevent these shortcomings of worn parts, submerged arc surfacing is used in place of replacement with new ones, which is economically beneficial.
Keywords: ceramic fluxes, surfacing, welding, melt, Scat.